The spread of viral infection in moths, - Roose, T; Maini, P; Cory, J; Hails, R (1995)
To control insect pests with a virus, it is important to determine the optimum time for the treatment. However, before analysing this problem, a realistic model for the uninfected host must be developed. A model framework for this has been developed and applied to the pine beauty moth which is a major pest of lodgepole pine in Scotland.